Papuaneon, a new genus of jumping spiders from Papua New Guinea (Araneae: Salticidae: Neonini) - Maddison, Wayne P. (Zootaxa, 2016)
The genus Neon Simon stands alone as a phylogenetically isolated astioid jumping spider, the only member of the Neonini. The new genus Papuaneon is established for the jumping spider Papuaneon tualapa sp. nov. from Papua New Guinea. Resembling a large, hirsute Neon, it is here shown to be the sister group to Neon, based on data from the nuclear 28S and Actin 5C, and the mitochondrial 16SND1 region. Photographs of living specimens are provided.